INFORMASI AKUNTANSI DAN NON AKUNTANSI PADA FENOMENA UNDERPRICING YANG TERJADI SAAT PENAWARAN UMUM SAHAM PERDANA PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Kurniawan, Lydia (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2014)
Abstract: In order to expand their business in several ways, for example companies canÃ‚Â offer their shares to the general public. Underpricing is a phenomenon that often appearsÃ‚Â and is experienced by companies that conduct an Initial Public Offering on the variousÃ‚Â stock exchanges in the world, where the IPO price is set lower than the true value of theÃ‚Â company. Underpriced shares often occur because of information asymmetry orÃ‚Â inequality of information that occurs in the group of investors who have information and a group of investors who do not have the information about the prospects of the issuer company. This study examined whether the age of the firm, firm size, and return onÃ‚Â assets (ROA) affect the level of IPO underpricing on the company at the IndonesianÃ‚Â Stock Exchange. This study was measured by Initial Return underpricing. The objects inÃ‚Â this study are 32 companies that did the initial public offering in 2002 to 2004 at theÃ‚Â Indonesia Stock Exchange and experienced under pricing . Conclusions from the studyÃ‚Â indicate that the companies age and their size variables are not shown to affect theÃ‚Â dependent variable Underpricing, while the variable Return on Assets (ROA) UnderÃ‚Â pricing are shown to affect the dependent variable at a significant level of 5%.